Predictors of recurrence of ventricular tachycardia and the effectiveness of endocardial ablation at the patients with sudden cardiac death and history of myocardial infarction - O. M. Grytsay; Ya. V. Skybchyk (Кардіохірургія та інтервенційна кардіологія, 2024)
The aim – to assess predictors of recurrence of ventricular tachycardia after the procedure of endocardial ablation in patients with an episode of cardiac arrest and history of myocardial infarction. Materials and methods. The work included 32 patients (average age 52.9 ± 5.6 years, 27 (84.3 %) men and 5 (15.6 %) women). Including criteria were: an episode of cardiac arrest with successful resuscitation, history of myocardial infarction, procedure of endocardial mapping with ablation the substrate of tachyarrhythmia. The duration of observation was 12 months. Patients were examined according to the guidelines of the diagnosis in patients with ventricular tachycardia. The endpoint was the recurrence of VT at the time of the patient’s last visit. Quantitative indicators are presented as mean ± standard deviation. Results. At 12 months after the procedure, the following parameters were associated with relapses of ventricular tachycardia with the greatest statistical significance: left ventricular systolic dysfunction (additive relative risk (ARR) – 43.0 %, relative risk (RR) – 2.57 [1.14–5.82], odds ratio (OR) – 6.50 [7.00–30.70], p < 0.05), arterial hypertension (ARR – 41.0 %, RR – 2.75 [1.08–6.90], OR – 5.96 [1.33–26.70], p < 0.05), diabetes mellitus (ARR – 43.0 %, RR – 2.83 [1.10–7.30], OR – 6.50 [1.25–33.60], p < 0.05), duration of arrhythmic history (ARR – 40.0 %, OR – 5.71 [7.00–28.10], p < 0.05), electrical storm episode at the time of ablation (ARR – 38.0 %, RR – 1.89 [1.27–4.99], OR – 8.57 [7.00–51.50], p < 0.05). Atrial fibrillation (ARR – 25.0 %, RR  – 1.58 [0.76–3.25], OR – 2.73 [7.00–17.60], p < 0.05), age younger than 45 years (ARR – 15.0 %, RR – 1.37 [0.60–3.07], OR – 1.78 [7.00–7.47], p < 0.05), and chronic obstructive pulmonary disease (ARR – 18.0 %, RR – 1.46 [0.71–2.99], OR – 2.10 [7.00–9.01], p < 0.05) were at the limit of probability with reliable odds ratio. Recurrent VT was recorded more often in patients with partial intraoperative effect than in those with complete effect (26.7 % versus 5.9 % of patients, p < 0.05). Recurrences of VT were also more common in patients with larger number of radiofrequency ablation procedures in the history (46.7 % versus 5.9 %). A significant risk factor for a recurrent episode of tachycardia was also the duration of corrected QT-interval (QTc, ms) and the presence of late potentials from the epicardial surface of the left ventricle. In the multivariate model, all the above-mentioned parameters were tested, while the only factor independently associated with VT recurrence was the fact of an electrical storm at the time of ablation (risk ratio 5.78; 95 % CI: 1.16–19.4; p = 0.02). Conclusions. Factors associated with an increased risk of recurrence of ventricular tachyarrhythmias in patients after a heart attack and an episode of sudden death include left ventricular systolic dysfunction, arterial hypertension, diabetes mellitus, and duration of an arrhythmic history. The presence of an electrical storm is an independent predictor of VT relapse when observed up to 12 months after endocardial ablation.